2005
DOI: 10.1074/jbc.m508939200
|View full text |Cite
|
Sign up to set email alerts
|

Conjugation of LG Domains of Agrins and Perlecan to Polymerizing Laminin-2 Promotes Acetylcholine Receptor Clustering

Abstract: Neuromuscular junction (NMJ) assembly is characterized by the clustering and neuronal alignment of acetylcholine receptors (AChRs). In this study we have addressed post-synaptic contributions to assembly that may arise from the NMJ basement membrane with cultured myotubes. We show that the cell surface-binding LG domains of non-neural (muscle) agrin and perlecan promote AChR clustering in the presence of laminin-2. This type of AChR clustering occurs with a several hour lag, requires muscle-specific kinase (Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Lmα4 levels were increased in both dy2J and Tg+dy2J muscle. integrin, and αDG; (b) Lm111 can fully rescue the severe dystrophy and peripheral neuropathy of the Lama2-KO mouse (33,34); and (c) a collection of α1-laminins bearing deletions and point mutations that affect specific functions have been generated, characterized, and previously used to dissect laminin functions in the laboratory (14,35,36). In addition, the assembly of WT recombinant Lm211, Lm411, and Lm511 was compared with that of Lm111.…”
Section: Resultsmentioning
confidence: 99%
“…Lmα4 levels were increased in both dy2J and Tg+dy2J muscle. integrin, and αDG; (b) Lm111 can fully rescue the severe dystrophy and peripheral neuropathy of the Lama2-KO mouse (33,34); and (c) a collection of α1-laminins bearing deletions and point mutations that affect specific functions have been generated, characterized, and previously used to dissect laminin functions in the laboratory (14,35,36). In addition, the assembly of WT recombinant Lm211, Lm411, and Lm511 was compared with that of Lm111.…”
Section: Resultsmentioning
confidence: 99%
“…By extension, these data indicate that DG, and more broadly the DGC, may function extracellularly in formation of NMJs. Recent studies have reported that inactive muscle agrin can be potentiated to stimulate AChR aggregation when complexed with laminin into an ECM (57,74). The association of ␣-DG with laminin, agrin, and perlecan may similarly facilitate the assembly of endogenous ligands to stimulate AChR aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Post-weaning maintenance of NMJ is mediated by the collagen IV isoform (Fox et al 2007;Nishimune et al 2008). Other stage-specific ECM organizers including laminin-211, perlecan, and agrin cooperatively mediate acetylcholine receptor clustering on the postsynaptic membrane (Smirnov et al 2005 ; Table 1), a process that is also critical for NMJ maturation and is further fine-tuned by WNT3 signaling both in vitro and in vivo (J. Henriquez et al 2008).…”
Section: Ecm Regulation Of Cartilage Developmentmentioning
confidence: 99%